EXercise to prevent AnthrCycline-based Cardio-Toxicity (EXACT) in individuals with breast or hematological cancers: a feasibility study protocol. Issue 1 (December 2016) - Keats, Melanie; Grandy, Scott; Giacomantonio, Nicholas; MacDonald, David; Rajda, Miroslaw; Younis, Tallal
Abstract Background Anthracyclines (AC), widely used and effective anticancer agents, are known to induce both acute and chronic declines in cardiovascular health, ranging in severity from asymptomatic, subclinical dysfunction to substantial cardiomyopathy leading to congestive heart failure and death. There is substantial evidence that physical activity, higher levels of cardiorespiratory fitness, and exercise therapy can help prevent cardiovascular disease. Moreover, animal studies have shown that exercise performed concomitantly with AC treatment may attenuate early cardiac damage that results from AC exposure. Our primary objective is to assess the feasibility of a 12-week aerobic exercise training (AET) program in patients receiving AC-based chemotherapy. Methods/design This is a prospective, single-arm (pre-post-test design), feasibility study of a supervised 12-week progressive, light-to-moderate to moderate-to-vigorous intensity AET program for patients (18–65 years) receiving AC chemotherapeutic treatment for a primary/non-recurrent breast cancer or hematological malignancy. Both feasibility (e.g., participant recruitment, program adherence, safety) and intervention outcome (e.g., biological markers of cardiotoxicity, aerobic capacity, quality of life) measures will be collected. The AET program will include two, 45-min community-based exercise sessions (treadmill or cycle) per week for a total of 12 weeks. All exercise sessions will be supervised by trained exercise specialists. Discussion Data from the EXACT study will be evaluated to determine the need to refine patient recruitment methods and general acceptability of the AET program. Preliminary data on the effects of the AET intervention on pertinent cardiac and health outcomes will also be evaluated and used to inform future studies in terms of the most appropriate outcome measure(s) to adopt and sample size estimation. Trial registration ClinicalTrails.gov, NCT02471053